The Application of Digital Intelligence to Real Estate Technology Service Quality: A Conceptual Model - Oluwatofunmi, Akinwamide David; Kolawole , Oyetunji Abiodun; Hahn, Jonas (Journal of Technology Management and Business, 2021)
The occurrence of this present global pandemic has further heightened the need for the full adoption and maximisation of digital technologies service-related activities within the built environment. For instance, the disruption in real estate transactions has since demanded digital technologies in its service delivery. With the adoption of real estate technologies (such as artificial intelligence, lease extraction technologies, Internet of Things, property passports, machine learning, automated valuation model, blockchain, and smart contracts, among others) for the global best practice, digital competencies, skills and attitudes are needed by real estate service providers to sustain the future of real estate transaction in the service industry. The new concept of digital intelligence is a set of skills needed by real estate service providers to meet digital technologies’ demand in real estate transactions and the digital world’s challenges. Incorporating this concept in real estate technology service quality would help fulfill customersâ€™ satisfaction, commitment, and retention in the service delivery. Therefore, this article is pertinent to review service quality models relevant to real estate service and develop a useful service quality model using digital intelligence in service delivery.